Cultural Character Analysis on Architectural Elements of the Chinese Temples’ Buildings before the 19th Century in Central Java - Mildawani , Irina; Darmawan, Djoko (Bina Nusantara University, 2023)
The research provided an in-depth exploration of the architectural nuances of pre-19th century Chinese temples in Central Java, Indonesia, emphasizing their cultural significance and relevance. A detailed examination of a range of temples identified unique architectural features that reflected a sophisticated synthesis of Chinese cultural elements and local Javanese traditions. Applying a qualitative method, the research integrated historical scrutiny with architectural analysis, meticulously examining stylistic attributes, construction methodologies, and decorative patterns typical of these temples. The key discoveries highlight an intricate amalgamation of traditional Chinese architectural principles with native materials and craftsmanship, culminating in a distinctive, hybrid architectural form. This fusion not only symbolizes the cultural convergence and assimilation between Chinese immigrants and the indigenous Javanese during the pre-colonial era but also underscores the role of these temples as pivotal preservers of Chinese cultural heritage in Java. Furthermore, the research contributes to a deeper understanding of the diversity within architectural practices and offers insightful perspectives on the historical and socio-cultural dynamics in Central Java. The novelty of the research is anchored in its focused examination of a historically and geographically specific context, its interdisciplinary and thorough approach, the revelation of a unique hybrid architectural style, and its significant insights into the cultural and sociological dimensions of Central Java’s architectural legacy.